Role of hydrogen and oxygen in the study of substrate surface impurities and defects in the chemical vapor deposition of graphene. (15th November 2021) - Zhang, Yanhui; Sui, Yanping; Chen, Zhiying; Kang, He; Li, Jing; Wang, Shuang; Zhao, Sunwen; Yu, Guanghui; Peng, Songang; Jin, Zhi; Liu, Xinyu
Abstract: Large-area and high-quality graphene grown on metal by chemical vapor deposition (CVD) has great potential applications in electronics and photo electronics. After more than 10 years of development, great progress has been made in the growth of graphene, and the role of various factors in the growth of graphene has been gradually clear. In this review, the role of hydrogen and oxygen in the formation and elimination of carbon-based impurities and silicon oxide particles and in the formation, observation, and control of grain boundary, point defects, and wrinkles is introduced. The content focuses on the specific experimental methods, results, and mechanism. Finally, the challenges of hydrogen and oxygen in the study of graphene growth on metal are introduced. This review can increase the theoretical knowledge and experimental design ability related to hydrogen and oxygen in CVD graphene grown on metal. Highlights: The concept of carbon-based impurity, silicon oxide particle, grain boundary, point defect and wrinkle, and their effects on the CVD graphene growth on metal are introduced in detail. The role and the mechanism of hydrogen and oxygen in the study of carbon-based impurities, silicon oxide particles, grain boundaries, point defects and wrinkles are introduced. We systematically share our experience and suggestions on the research of impurities and defects in CVD graphene growth on metal.